Determinants and outcomes of price premium and loyalty: A food case study. Issue 1 (29th October 2017) - Gómez, Mar; Martín‐Consuegra, David; Díaz, Estrella; Molina, Arturo
Abstract: This paper examines determinants and outcomes of price premium and loyalty on a food product. The study attempts to fill this gap by offering new insights into consumer's perspectives, as concerns food marketing, and to empirically test a model that includes five determinants or drivers: awareness, corporate social responsibility, origin, quality, and positioning. Furthermore, the greater or weaker impact of price premium and loyalty on their outcomes have been also studied, specifically, the influence that word‐of‐mouth has on people's opinions. This study uses a survey research design, and the data were collected from 278 consumers of a specific food product: olive oil. Structural equation modeling with partial least squares regression technique was used to test the hypotheses. The results provide empirical support for the proposed differences on the relationships of price premium and loyalty with their determinants and outcomes. Positioning is the strongest and unique element of the determinants of price premium. Awareness, corporate social responsibility, and quality are the drivers of loyalty. Both constructs have a positive influence on word‐of‐mouth. The findings reveal important practical implications for food managers, in terms of making a proper design of strategies from the analysis of consumer's behavior. To stay competitive, practitioners should work in an ongoing process. Specifically, they should pay attention to quality, sustainable olive oil, locally made products, or food marketing.